How are employees engaged to the brand where they work for? - Silva, Catarina Isabel Neves Pereira da (2019)
In the last decade, companies have been started to give more importance to employees, recognized them as a competitive advantage and pursuing organization tools to engage them. This study intends to analyse the influence and effects of employees’ engagement on relationship employee/brand, through understanding if employees act as customers engaged of the brand where they work and if they conduct employee brand equity. As a last challenge, realize if they are capable of being voluntary brand ambassadors, increasing in this way the brand reputation and awareness. A quantitative analysis was carried out with the aim to develop and measure employee engagement and these effects in four Portuguese big companies. The results demonstrated that employee’s identification, commitment and loyalty, represent a significant role in employee engagement who promote brand positive behaviours. Through the findings of the study, we gathered that managers and marketers should focus their efforts to create and maintain engaged employees in order to conduct effectively employees’ positive behaviours through the brand, and consequently generate brand ambassadors.